Groundwater Flow Modeling in Chitwan Dun Valley (Between Narayani River and Lothar Khola), Nepal - Bhandari, Rita; Pathak, Dinesh (Journal of Institute of Science and Technology, 2019)
Models are simplification of reality to investigate certain phenomena or to predict future behavior and always tries to generate scenario that is close to the real condition. Groundwater flow models are computer models generated through using established flow equations that simulate and predict aquifer conditions. The result of groundwater modeling is used for groundwater management and remediation. In the present study, hydrostratigraphic units were identified through interpreting the lithological logs of the drilled wells then fence diagram was prepared with three major aquifer horizons, namely unconfined, shallow confined and deep confined aquifers. In addition, hydrogeologic data were integrated to develop a conceptual hydrogeologic model of the aquifer system of the Chitwan Dun valley, which was the basis for the development of the numerical model. The aquifer system was modeled numerically using MODFLOW-2005 numerical modeling, which was further calibrated and an acceptable numerical model was obtained which showed different flow direction in each aquifer layer. The model was validated by comparing the observed and simulated heads. The result shows that in each of the aquifer layers, the general flow direction is towards west and south-west.